Analysis of soil behavior in terms of compaction, expansion and penetration resistance with the addition of kraft paper (Research, Society and Development, 2020)
This research has as goal to present the experimental study of soil behavior with the addition of crushed cement bags, known as kraft paper, cement bag residue. For the analysis, the soil was collected in a deposit and the initial processes for the characterization tests were carried out, being the sieve size analysis (AGP), liquidity limit (LL) and plasticity limit (LP) that allows us to classify you as to the type of soil being studied. Compaction tests and the CBR known as the California Support Index (ISC) were carried out. In the tests the behavior of the soil of the city of Teresina - PI was verified with the addition of these residues trying to maintain the initial quality or improving the resistance capacity of the soil. The tests were carried out for natural soil (without addition) and with additions of 1%, 2% and 3% of crushed kraft paper. In the results, it was observed that when adding the percentages there were no significant changes in the degree of soil compaction, in the expansion or in the resistance to penetration of the piston in the soil, these positive results for these residues to be mixed with soil and compacted without changing the performance and technical quality. The analysis of the results, through the compaction test and CBR, showed that there are possible possibilities for the use of kraft paper crushed in compacted landfills.